Benefits and limitations of implementing Chronic Care Model (CCM) in primary care programs: A systematic review. (1st May 2018) - Yeoh, E.K.; Wong, Martin C.S.; Wong, Eliza L.Y.; Yam, Carrie; Poon, C.M.; Chung, Roger Y.; Chong, Marc; Fang, Yuan; Wang, Harry H.X.; Liang, Miaoyin; Cheung, Wilson W.L.; Chan, Chun Hei; et al.
Abstract: Background: Chronic Care Model (CCM) has been developed to improve patients' health care by restructuring health systems in a multidimensional manner. This systematic review aims to summarize and analyse programs specifically designed and conducted for the fulfilment of multiple CCM components. We have focused on programs targeting diabetes mellitus, hypertension and cardiovascular disease. Method and results: This review was based on a comprehensive literature search of articles in the PubMed database that reported clinical outcomes. We included a total of 25 eligible articles. Evidence of improvement in medical outcomes and the compliance of patients with medical treatment were reported in 18 and 14 studies, respectively. Two studies demonstrated a reduction of the medical burden in terms of health service utilization, and another two studies reported the effectiveness of the programs in reducing the risk of heart failure and other cardiovascular diseases. However, CCMs were still restricted by limited academic robustness and social constraints when they were implemented in primary care. Higher professional recognition, tighter system collaborations and increased financial support may be necessary to overcome the limitations of, and barriers to CCM implementation. Conclusion: This review has identified the benefits of implementing CCM, and recommended suggestions for the future development of CCM. Highlights: This systematic review analysed Chronic Care Models for cardiovascular diseases. Most studies reported outcome improvements and patient compliance with treatment. Some studies demonstrated reduction of medical burden, like healthcare utilization. They are effective to reduce risk of heart failure & other cardiovascular diseases. They are restricted by academic robustness and social constraints in primary care.